Cognitive impairment in adults under compulsory psychiatric care: association with psychotic symptoms and high-dose antipsychotics - Karanikola, Maria; Nystazaki, Maria; Kaikoushi, Katerina; Middleton, Nicos; Chatzittofis, Andreas (My University, 2023)
There is limited evidence on the association between cognitive function, psychotic symptoms and doses of antipsychotics in adults under compulsory psychiatric care.
Keywords: Cognitive impairment; involuntary hospital admission; Montreal Cognitive Assessment; polypharmacy; psychotic disorder